Modern requirements for refrigeration agents in transport air conditioners (Transport systems and technologies, 2025)
The Scientific advances, changes in national legislation in the field of combating the effects of global warming and market requirements have stimulated the development of fourth generation refrigerants. In contrast to the first and second generation refrigerants, which provided, along with the principle possibility of achieving a refrigerating effect, such qualities as durability and operational safety, the third and fourth generations include environmental constraints in a significant way. The identification of a link between leaks of traditional second-generation chlorofluorocarbon (CFC)-based refrigerants and the destruction of the protective atmospheric layer of ozone gave rise to the third generation of refrigerants. The Vienna Convention and the Montreal Protocol were the reaction of the world community, leading to the banning of ozone-depleting substances (ODS). At the same time, hydrochlorofluorocarbons were considered as temporary or transient and hydrofluorocarbons (HFCs) as long-term working bodies. Interest in the natural refrigerants ammonia, carbon dioxide, hydrocarbons and water has increased dramatically.
Keywords: railway transport; refrigerant; transportation air conditioners; greenhouse effect; alternative refrigerants; passenger car; refrigeration machine